Experiences of men undergoing prostate cancer screening at a hospital in Gauteng, South Africa - Boitumelo M. Komane; Anna Mosalo (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Prostate cancer is a global concern and a leading cause of death among men. Screening for prostate cancer is crucial for early detection and to mitigate advanced disease and high-cost treatments. However, men are not well informed about the disease and tend not to be supported during prostate cancer screening.